Surgical aspects of abdominal aortic aneurysm: literature review (Research, Society and Development, 2023)
This study aimed to understand the pathology of abdominal aortic aneurysm and possible surgical considerations in emergency settings. Analyzing the possible etiological factors contributing to the evolution of the aneurysm process in the abdominal aorta. This is a critical and analytical narrative review of research on surgical management of abdominal aortic aneurysms, taking into account the disease's morbidity and mortality levels and the most comfortable prognosis for the patient. A search for articles was carried out in the databases Medical Literature Analysis and Retrieval System Online (MEDLINE), Scientific Electronic Library Online (SciELO) and PubMed, with the following Health Sciences Descriptors (DeCS): Aneurysm; Aorta; Surgery; Dilation; Break. Selecting articles between the periods of 2005 to 2023, in English, Portuguese, German and Spanish, to increase the level of relevance and quality of the review. Endovascular repair of abdominal aortic aneurysms has proven to be a highly lethal pathology, mainly related to risk factors. It is assumed that over the decades, the number of smokers and obese people will increase, in this proportion, cardiovascular diseases will be responsible for greater social damage. In this context, endovascular repair appears as a viable alternative for these patients, which can have an extreme influence on their lives.